Live Cell Imaging of RhoGTPase Biosensors in Tumor Cells - Bravo-Cordero, Jose Javier (2013)
Tumor cell motility and invasion rely on actin cytoskeleton rearrangements mediated by the activation of RhoGTPase signaling pathways. Invadopodia are membrane-degrading protrusions that mediate extracellular matrix degradation. Here, we provide procedures for imaging RhoGTPase biosensors in tumor cells during the formation of invadopodia and matrix degradation.